Professional Practice Issues - Leifso, Genelle (Operating Room Nurses Association of Canada Journal, 1998)
The value in exploring nursing issues was publicly demonstrated in 1997 when Winnipeg perioperative nurses told of their struggle with the personal impact of professional practice issues in their workplace. Nursing issues are matters of dispute within and affecting the nursing profession. Issues evolve because of value differences which emerge as part of one’s socialization process or develop as a by-product of one’s life experience. The author revisits a personally experienced nursing issue and explores it according to Bowman’s plan.